DMG case: State responsibility suitableof compensation for group action - Díaz G., Luis Bernardo (Universidad Pedagógica y Tecnológica de Colombia, 2014)
This is an analysis of the breach of legitimate expectation of cardholders who invested their money in DMG Trade Company and they did so based on the legitimate confidence that the President during two communal councils inspired them, since he invited them to invest in that company and also because one of his sons made part of one of the companies of the holding. As a result of State intervention, by the strength of Grupo Aval and its Chairman, and because of the State refusal to return all their investments and revenues, there is a State responsibility suitable of compensation for group action.